Multiliteracies in Writing Class - Umi Rokhyati (Ahmad Dahlan Journal of English Studies, 2014)
AbstractMultiliteracies in language teaching can make the process of teaching language easier, more interesting and better. This can include the use of technology in the classroom. To apply multiliteracies in the classroom both students and teachers must be multiliterate.In writing class, multiliteracies can be applied by using computer and internet in the teaching and learning process. It can be applied in three steps: preparation, implementation, and evaluation. In preparation step the teacher can find sources of teaching material from textbooks and browsing in the internet. Then, he/she can use power points when presenting the teaching material, giving exercises and task. In the last step, evaluation, the teacher gives an assignment and the students should submit their work via email to the teacher. The teacher then gives some feedback using computer (comment bar) and send it back to the students. The students must revise the work based on the teacher's feedback and send again to the teacher. This way of teaching is more interesting for the students, more efficient and therefore can give better result in learning.